Correlation between Compressive Strength and Cement Content in Soil-Cement Blocks (International Journal of Geoscience, Engineering and Technology, 2025)
This study investigates the correlation between the compressive strength of soil-cement blocks and the cement content in their mixture. A systematic literature review was conducted, collecting data from 12 scientific articles, resulting in 87 studies. The selected studies provided important information on the cement content, compressive strength, and casting characteristics of the blocks. The data were organized and statistically analyzed using Microsoft Excel 2019. A linear regression model was applied to evaluate the relationship between cement content and compressive strength measured at 28 days of curing. The results indicate a positive correlation (Pearson's correlation coefficient, r = 0.589) as described in the literature, suggesting that increasing cement content generally improves compressive strength. However, the results also reveal that other factors, such as soil type, compaction pressure, curing conditions, and moisture content, significantly influence the improvement in block performance. This research contributes to the optimization of soil-cement formulations, promoting more sustainable construction practices, minimizing cement consumption, and ensuring structural integrity. Limitations of the study include the variability in experimental conditions between the reviewed studies and the reliance on secondary data. Future research should incorporate experimental investigations to validate and expand on these results.